2015
DOI: 10.1002/hbm.22796
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia‐like topological changes in the structural connectome of individuals with subclinical psychotic experiences

Abstract: Schizophrenia is often regarded as a “dysconnectivity” disorder and recent work using graph theory has been used to better characterize dysconnectivity of the structural connectome in schizophrenia. However, there are still little data on the topology of connectomes in less severe forms of the condition. Such analysis will identify topological markers of less severe disease states and provide potential predictors of further disease development. Individuals with psychotic experiences (PEs) were identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 76 publications
2
55
0
Order By: Relevance
“…Autistic traits [84,85] and some [86,87] (but not all [86]) markers of poor social cognition are also associated with increased risk of PEs. These findings, along with evidence of brain structural differences and dysfunctional connectivity [88] lend support to the thesis that early life exposures can have subtle impacts on cerebral development, cognitive function, and onset of PEs in keeping with the neurodevelopmental hypothesis of schizophrenia.…”
Section: Understanding Aetiology Of Pesmentioning
confidence: 49%
“…Autistic traits [84,85] and some [86,87] (but not all [86]) markers of poor social cognition are also associated with increased risk of PEs. These findings, along with evidence of brain structural differences and dysfunctional connectivity [88] lend support to the thesis that early life exposures can have subtle impacts on cerebral development, cognitive function, and onset of PEs in keeping with the neurodevelopmental hypothesis of schizophrenia.…”
Section: Understanding Aetiology Of Pesmentioning
confidence: 49%
“…Graph theory analyses of brain-related networks have led to possible investigations of whole-brain functional connectivity (fMRI), white-matter connectivity (DTI), and gray matter covariance analyses (GM) in both healthy and populations with a CNS disease or disorder [9, 24-25]. Therefore, this method has the capacity to investigate the brain at its different levels as a whole.…”
Section: Network Analysis and Graph Theory Applicationsmentioning
confidence: 99%
“…15 Such graph-based network studies capture an important aspect of developmental maturation that is crucial for understanding the pathophysiology of psychotic disorders. 19,20 Previous studies reported reduced small-worldness of structural brain networks in patients with schizophrenia, [21][22][23] CHR individuals, 24 people at increased familial risk for schizophrenia, [25][26][27] and those with subclinical psychotic experiences, 28 characterized by increased segregation and decreased interaction of anatomical covariance (see the published reviews 18,19,[29][30][31] of network analyses in schizophrenia). Of various regional morphometric properties that can be assessed for structural covariance, gyrification is a compelling marker of early neurodevelopment.…”
mentioning
confidence: 99%